First isolation and nucleotide comparison of the gag gene of the caprine arthritis encephalitis virus circulating in naturally infected goats from Argentina - Panei, Carlos Javier (2017)
Caprine arthritis encephalitis virus (CAEV) has been reported in different countries worldwide, based on serological and molecular detection. In Argentina, the prevalence of CAEV infections is increasing, with goats showing symptoms associated mostly with cachexia and arthritis. Although in Argentina the virus has been detected by serology, it has never been isolated or characterized. Thus, the objectives of this work were to isolate and analyze the nucleotide sequences of the gag gene of Argentine CAEV strains and compare them with those of other SRLVs previously reported. Nucleotide sequence comparison showed homology with CAEV-Co, the CAEV prototype. Phylogenetic analyses showed that the Argentine strains clustered with genotype B, subtype B1. Because the molecular characterization of the gag region is suitable for phylogenetic studies and may be applied to monitor the control of SRLV, molecularly characterizing the Argentine CAEV strains may help develop a proper plan of eradication of CAEV infections.